A review of research on the effects of early childhood education and care (ECEC) on child development - Melhuish, E; Ereky-Stevens, K; Petrogiannis, K; Ariescu, A; Penderi, E; Rentzou, K; Tawell, A; Slot, P; Broekhuizen, M; Leserman, P (CARE - European Early Childhood Education and Care, 2015)
This report considers international research on the impact of Early Childhood Education and Care (ECEC) provision upon children’s development, using studies reported from a wide range of sources including journals, books, government reports and diverse organisation reports.